Collaborative governance in light rail transit services in Palembang city: A multi-helix perspective - Asteriniah, Femi; Wijaya, Andy Fefta; Hermawan, Hermawan; Danar, Oscar Radyan (Edelweiss Applied Science and Technology, 2025)
This study examines the application of collaborative governance in the management of Light Rail Transit (LRT) services in Palembang City, Indonesia. Using Emerson and Nabatchi’s collaborative governance framework integrated with a multi-helix approach, this research analyzes the dynamics of collaboration between various stakeholders in the provision of LRT services. Through qualitative analysis of interviews with key stakeholders, this study identified significant challenges in collaborative processes, including uncontrolled uncertainty, inadequate interdependence, limited consequential incentives, and inadequate initiative leadership. Research findings reveal that weak principal engagement, limited shared motivation, and uneven capacity for joint action have hindered effective collaboration. This research contributes to the literature on collaborative governance in public transport management and provides practical recommendations for improving LRT services through increased stakeholder collaboration.